REUSABILITY: A MAJOR ASPECT TO MAINTAINABILITY (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper focuses on Reusability.  Reusability is one of the most significant software quality  indicator its correct quantification directs to the prospects of  facilitating as well as improving software maintenance  process. Reusability is strongly related to maintainability  and constantly plays a key role to deliver high class  maintainable and trustworthy software within time and  budget. In this paper an endeavor has been made to establish  a correlation between object oriented design constructs and  Reusability. A Reusability Quantification Model (RQMOOD)  has been proposed for Object Oriented Design by using  multiple linear regression. Finally, the proposed model has  been validated using experimental tryout.
Keywords: Maintainability; Modularity; Reusability; Testability; Design phase; Object Oriented Design